2013
DOI: 10.1590/s1516-14392013005000006
|View full text |Cite
|
Sign up to set email alerts
|

Platinum uptake from chloride solutions using biosorbents

Abstract: Present work investigates platinum uptake from synthetically prepared, dilute platinum-bearing solutions using biomass residues, i.e. pistachio nut shell and rice husk, which are abundant in Turkey, and provides a comparison between these two biosorbents. Effects of the different uptake parameters, sorbent dosage, contact time, temperature and pH of solution on platinum uptake (%) were studied in detail on a batch sorption. Before the pistachio nut shell was activated, platinum uptake (%) was poor compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Several appropriate technologies are available including precipitation (Safdar et al, 2011), solvent extraction (Hung et al, 2007;Shamsipur et al, 2009), membrane filtration (Borbély and Nagy, 2009;Trivunac and Stevanovic, 2006;Xiang Li et al, 2013), cementation (Aktas, 2011(Aktas, , 2012Morcali et al, 2013c), ion exchange (Godlewska-Żylkiewicz et al, 2000;Shen et al, 2010Shen et al, , 2011 and adsorption (Fırlak et al, 2013;Kyzas et al, 2013;Wang et al, 2011). Comparatively, adsorption seems to be the most suitable as large volumes of very dilute wastes can be treated economically and nearly no waste residue is produced (Morcali et al, 2013a). A number of adsorbents have been developed and tested for the recovery of precious metals such as activated carbon (Aktas and Morcali, 2011b;Navarro et al, 2006), membranes (Xiang Li et al, 2013), and chelating resins (Atia et al, 2005;Birinci et al, 2009;Shen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several appropriate technologies are available including precipitation (Safdar et al, 2011), solvent extraction (Hung et al, 2007;Shamsipur et al, 2009), membrane filtration (Borbély and Nagy, 2009;Trivunac and Stevanovic, 2006;Xiang Li et al, 2013), cementation (Aktas, 2011(Aktas, , 2012Morcali et al, 2013c), ion exchange (Godlewska-Żylkiewicz et al, 2000;Shen et al, 2010Shen et al, , 2011 and adsorption (Fırlak et al, 2013;Kyzas et al, 2013;Wang et al, 2011). Comparatively, adsorption seems to be the most suitable as large volumes of very dilute wastes can be treated economically and nearly no waste residue is produced (Morcali et al, 2013a). A number of adsorbents have been developed and tested for the recovery of precious metals such as activated carbon (Aktas and Morcali, 2011b;Navarro et al, 2006), membranes (Xiang Li et al, 2013), and chelating resins (Atia et al, 2005;Birinci et al, 2009;Shen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that PVA/MA/ ATM NFm was very effective for the removal of Pt (IV) and Pd(II) from waste solutions, and the maximum adsorption capacity (Q max ) of PVA/MA/ATM NFm was comparable to those of other adsorbents presented in scientific literature (Fujiwara et al 2007;Peng et al 2009;Kavaklı et al 2006;Lin and Lien 2013;Birinci et al 2009;Fayemi et al 2013;Morcali et al 2013b;Morcali et al 2013b;Morcali et al 2013c). Maximum adsorption capacity was obtained at lower pH values, and this becomes an advantage, due to the fact that sorbents have no or low affinity for metals, particularly in strong acidic solutions.…”
Section: Comparison With Other Adsorbentsmentioning
confidence: 67%
“…make chloro complexes in a lower pH. However, the solution pH was increased up to 1.5 to easily catch the metal ions in the complex form (Aktas and Morcali 2011b; Morcali et al 2013c;Morcali et al 2014b).…”
Section: The Effect Of Phmentioning
confidence: 99%
“…Palladium can be recovered from aqueous system using several different methods, amount of them electrochemical [2][3][4], chemical [5], adsorption and/or ionic exchange [6,7].…”
Section: Introductionmentioning
confidence: 99%